Kindler's syndrome: A tale of two siblings - Navya Handa; Dilip Kachhawa; Vinod Kumar Jain; Pankaj Rao; Anupam Das (Wolters Kluwer Medknow Publications, 2016)
Kindler's syndrome (KS) is a rare inherited skin disease characterized by acral blistering, photosensitivity, progressive poikiloderma, and cutaneous atrophy along with different types of mucosal involvement. We hereby report KS in two siblings. The case is being reported for its rarity and for emphasizing the importance of considering this condition in the differential diagnosis of disorders that may cause blistering, cutaneous atrophy, and/or poikilodermatous skin changes. Besides, the presentation of the disease in two of the members of the same family makes the case even more interesting.